Review on OFDM: Concept, scope and its application - Malik, Rizwan Ahmed; Shabir, Shahid; Singla, Ruchi (International Journal of Computer Sciences and Engineering, 2025)
Orthogonal frequency division multiplexing(OFDM) is the case of multicarrier transmission in which a single data stream is transmitted over a number of subcarriers of lower rate. OFDM is a modulation format that is being used in latest wireless and telecommunications standards. OFDM has been adopted in the Wi-Fi arena where the standard like 802.11a, 802.11n, 802.11ac. It has been chosen for the cellular telecommunication standard 4G LTE. OFDM has been adopted for a number of broadcast standards from DAB digital radio to the digital video broadcast standards, DVB. OFDM effectively reduce the inter-symbol interference(ISI) caused by the delay spread of wireless channels. OFDM has been used in both wired and wireless communication medium. One of the major drawback of OFDM is its peak to average power ratio(PAPR). In this paper we are going to discuss basics of OFDM techniques, scopes, losses and its application.